Principles of surveying - Herubin, Charles A. (Virginia : Prentice-Hall, 1978)
This book is intended for colleges and technical schools and is designed to facilitate self-study.
One. Introduction -- Two. Accuracy and error -- Three. Horizontal distances -- Four. Vertical distances -- Five. Measuring angles -- Six. The traverse -- Seven. Stadia surveying and mapping -- Eight. Construction surveys-general -- Nine. Construction surveys dealing with slopes -- Eleven. Employment in the surveying field.
Includes bibliographical references and index.
Keywords: SURVEYING